2013
DOI: 10.1002/jobm.201200218
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of a novel acid phosphatase from the split gill mushroom Schizophyllum commune

Abstract: A monomeric acid phosphatase (ACP) with a molecular mass of 72.5 kDa was purified from fresh fruiting bodies of cultured Schizophyllum commune mushroom. The isolation procedure entailed ion exchange chromatography on DEAE-cellulose, CM-cellulose, and Q-sepharose, and gel filtration by fast protein liquid chromatography on Superdex 75. It demonstrated a unique N-terminal amino acid sequence of NAPWAQIDEV, which exhibited 60% amino acid identity to that of S. commune hypothetical histidine ACP based on its genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Our results revealed that the substrate affinities were in the low micromolar range with up to twofold differences; K cat values differed by up to 2.5‐fold. The K M values we determined are lower than those measured for acid phosphatases from different sources using classical spectrophotometric assays (Reilly et al ., 2009; Zhang et al ., 2013; Wang et al ., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Our results revealed that the substrate affinities were in the low micromolar range with up to twofold differences; K cat values differed by up to 2.5‐fold. The K M values we determined are lower than those measured for acid phosphatases from different sources using classical spectrophotometric assays (Reilly et al ., 2009; Zhang et al ., 2013; Wang et al ., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…2932 More importantly, LDH, GOx and HRP display significant reduction of catalytic activities at 50 °C, while the activity of Lip and AP is rapidly decreases above 40 °C. 8,3335 Methods to stabilize these enzymes so that they can function at high temperatures are needed to enhance their catalytic activities and is a challenge that should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Various methods have been used to purify relatively large numbers of protein molecules, while separation is often affected by the differences of the target protein and the properties of other substances present in the sample, such as solubility, precipitation, size, polarity, and the binding affinity of ammonium sulfate/acetone/ethanol precipitation followed by ultrafiltration, ion exchange, and gel filtration chromatography (Vohra and Satyanarayana, 2003;Boyce and Walsh, 2007). Therefore, combinations of two or more methods are commonly used for the purification of fungal phytases (Zhang et al, 2013a; TABLE 1 | Types of fermentation and substrates for fungal phytase production.…”
Section: Purification and Characterization Of Fungal Phytasesmentioning
confidence: 99%